2015
DOI: 10.1371/journal.pone.0120812
|View full text |Cite
|
Sign up to set email alerts
|

YCZ-18 Is a New Brassinosteroid Biosynthesis Inhibitor

Abstract: Plant hormone brassinosteroids (BRs) are a group of polyhydroxylated steroids that play critical roles in regulating broad aspects of plant growth and development. The structural diversity of BRs is generated by the action of several groups of P450s. Brassinazole is a specific inhibitor of C-22 hydroxylase (CYP90B1) in BR biosynthesis, and the application use of brassinazole has emerged as an effective way of complementing BR-deficient mutants to elucidate the functions of BRs. In this article, we report a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…33 Protein measurements were performed using a Protein Assay Kit (Bio-Rad, Hercules, CA, USA) and bovine serum albumin as a standard. The relative purity of recombinant CYP90D1 was estimated by SDS-polyacrylamide gel electrophoresis (12% polyacrylamide) and gel staining was performed using Coomassie brilliant blue R250.…”
Section: Expression and Purification Of Recombinant Cyp90d1mentioning
confidence: 99%
See 3 more Smart Citations
“…33 Protein measurements were performed using a Protein Assay Kit (Bio-Rad, Hercules, CA, USA) and bovine serum albumin as a standard. The relative purity of recombinant CYP90D1 was estimated by SDS-polyacrylamide gel electrophoresis (12% polyacrylamide) and gel staining was performed using Coomassie brilliant blue R250.…”
Section: Expression and Purification Of Recombinant Cyp90d1mentioning
confidence: 99%
“…33 The data obtained were used to calculate binding constants based on linear regression analysis. Spectral determinations were performed at least twice for each experiment, confirming the reproducibility with respect to the spectral profile and position of λmax and λmin.…”
Section: Binding Assay Of Propiconazole To Recombinant Cyp90d1mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently reported that new triazole-type inhibitors based on a ketoconazole scaffold (YCZ18) inhibit a new target, CYP90D1, in Arabidopsis. 38) Aside from BR synthesis inhibitors, BR antagonists have recently been developed. BL binds to BRI1 and functions as its most potent agonist.…”
Section: Pgrs For Regulating Br Activitiesmentioning
confidence: 99%